Role of In-service Training to Professional Competencies of Sports Science Lecturers in the Malaysian universities - Ali Ibrahim Ali Daw (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
Competencies acquired through in-service training professional skills of academic staff and enhances various teaching competencies, experiences, and professional qualification. Competencies of Malaysian lectures in sports science were evaluated based on their participation in planning instruction, conducting, instructing, and evaluating instruction to facilitate students' growth using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Results show that the convergent validity for all the loadings was statistically significant. The critical ratios (t-values) were significant at 0.05 level. Research findings showed that in-service training program among sports science lecturers in Malaysian universities improves lectures' professional competencies and enhances teaching skills and experiences that facilitate students’ growth. Findings showed that all constructs that were measured were significant and supported that in-service training services provided a promotional opportunity to advance university lecturers' professional competencies and experiences required for effective teaching services. Therefore, recommended that appropriate measures should be taken to integrate in-service training programs in Malaysian universities.